(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Khushwant Singh is a prolific writer in English. His writings are lively and very famous. He has written novels like-train to Pakistan, I shall not hear the nightingale, Delhi, The company of women, The Burial at sea and some important short stories like the voice of God. A Bride for the sahib and Black Jasmine. No doubt, he is a convenient writer. He is convenient because he does not compel a wider reading. He has declared that his roots are in the dunghill of tiny Indian villages. His fiction reeks with the odour of his roots. His style is hard and vigorous. He employs colorful Punjabi expletives and terms of abuse off and on. His Irony works like. Sikh swords.